Pendekatan Population Centered Health Nursing Care Terhadap Peningkatan Kemampuan Petani dalam Penanganan Trauma di Pertanian - Maisyaroh, Arista; Widianto, Eko Prasetya; Fibriansari, Rizeki Dwi; Sholeha, Lailatul; Handayani, Novita Tri (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Agricultural tools and machinery are currently widely used in agriculture to increase productivity. However, therate of trauma due to their use is still high; farmers are limited in handling trauma events in agricultural areas,leading to an increased risk of morbidity and mortality. This research aims to improve farmers' ability toperform trauma wound treatment of farming areas using the Population Centered Health Nursing Care (CHNC)approach. The study used an experimental, quasi design pre and post. The group treated 125 farmers fromCandipuro and a control group of 125 farmers from Pasirian, Tekung, Senduro, and Sumbersuko. The bivariateanalysis results using the Mann-Whitney U test on the treatment group obtained a significant value of 0.000(p<0,05). The test results differed from the control group, which did not have a substantial amount of 0.334 (p>0.05). It was concluded that increasing the ability of farmers after being given training was through thePopulation Centered Health Nursing Care approach. Developing a model for improving farmer safety is carriedout by developing health cadres in farmer groups.